Peningkatan Kapasitas Guru Geografi Memanfaatkan Media Pembelajaran Online dan Offline di Masa Covid 19 - Siti Dahlia; Tricahyono NH; Agung Adiputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia is one of country has impact of the virus Corona 19. The goverment give recommendation for community to do physical distancing as effort breaking the chain of transmission. That condition has impact for education sector, it is the school close. Based on that, the learning process is done remotely from home. This condition raises problems related to learning methods. The aim of this articel to discuss how to improve capacity of geography teacher utilizing online and offline learning in the Covid 19 periode. The method was conducted on the programme that is lecture, workshop, and discuss. The program was carried out on 22 April, 2020 with the zoom application. The participants in the event consisted of 47 teachers. The result of programme discussed about the problem of study frome home, learning project, kinds of learning platform of online and offline, and Ina Risk aplication. To motivating of students and also reduce the saturation on the learning process the teacher can also be done with multimedia-based games such as: Monopoli, Work Sheet, Instagram, and Snakes and ladders games.